The Role Model of Legal Protection for Pharmacists in Carrying Out Their Profession in Reviewed from Law No. 17 of 2023 Concerning Health - Sembiring, Tamaulina Br.; Iswahyudi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of the Indonesian State is to realize social welfare, especially in the health sector. Article 28 H paragraph (1) and Article 34 paragraph (3) of the 1945 Constitution of the Republic of Indonesia mandate that everyone has the right to welfare and health services, and the state is responsible for providing adequate public facilities and health services. This article uses literature review methods and normative legal research with a legislative approach to examine the legal system related to pharmacist protection. The research results show that there are no statutory regulations that specifically discuss protection for pharmacists in carrying out their practice. Therefore, regulations with heavier sanctions are needed to provide legal certainty for pharmacists and the public. The government needs to monitor pharmacies' compliance with pharmaceutical service standards, improve ongoing training, and update regulations to provide stronger legal protection for pharmacists. Further research is needed to evaluate policy implementation, risk analysis, and error management, as well as explore the role of technology in improving the quality of pharmaceutical services.